Penyelesaian Kredit Macet Melalui Upaya Litigasi di Koperasi Simpan Pinjam Surya Mandiri di Kabupaten Gianyar - I Putu Surya; I Nyoman Sukandia; Ni Komang Arini Styawati (Jurnal Interpretasi Hukum, 2021)
Economic developmentin era globalization increasing, with finance becoming necessity for every human being. research problems are: What factors cause bad credit at Surya Mandiri Savings and Loans Cooperative Gianyar Regency and how bad credit settlement efforts through litigation at Surya Mandiri Savings and Loan Cooperative Gianyar Regency This type research used Empirical Law. the factors that cause bad credit in cooperatives are internal factors that cause bad credit originating from the cooperative itself, external factors are factors that cause bad credit originating from customer side. Non-litigation is settlement of disputes outside the court that closed to public and the confidentiality of the parties guaranteed. Litigation dispute resolution is dispute resolution carried out through the court. It can be concluded that factors that cause bad credit at Surya Mandiri Savings and Loan Cooperative in Gianyar Regency are internal factors and external factors. The settlement of bad credit at Surya Mandiri Savings and Loan Cooperative in Gianyar Regency can be done by non-litigation and litigation. should not only pursue profit, but must be more assertive and apply the principle of prudence and Head of the cooperative credit department must be more careful providing loans to borrowers.